2013
DOI: 10.14478/ace.2013.1066
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Induction Effects of GABA Coated Rice from Fermentation of Mono Sodium Glutamate

Abstract: GABA는 포유류의 신경전달물질의 분비를 억제하며, 신경안정 작용, 스트레스 해소, 우울증 완화, 불면 등에 효과가 있는 것으로 알려져 있다. 곡류식품에 존재하는 GABA 함량은 일반미 1∼4 mg/100 g, 현미 4∼8 mg/100 g으로 알려져 있지만, 그 함량이 낮아 자연 식품으로부터 섭취하는 양으로는 생리활성을 기대하기 어렵다. 본 연구에서는 mono sodium glutamate (MSG)발효로 얻은 GABA 코팅 쌀이 신경안정제 뿐만 아니라 수면유도제로 쓰이는 melatonin과 serotonin의 생성 촉진 효과를 알아보았다. 그 결과 melatonin의 경우 GABA (25 mg/mL) 투여군은 3.515 ± 0.149 pg/mL, 일반 미 공급군의 경우 2.632 ± 0.188 pg/mL이며, GABA 코팅 쌀 공급군은 3.578 ± 0.158 pg/mL로 나타났다. Serotonin 함량 을 측정한 결과 GABA (25 mg/mL), 일반미 공급군은 각각 5.183 ± 0.142 ng/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…GAD genes are discovered in the gut microbiome, and GABA-producing probiotic strains affect health and behavior in animal models. GABA’s sleep-inducing impact has also been demonstrated in animal studies, which revealed that a group fed GABA-containing milk produced more melatonin and serotonin, both of which are regarded as sleep inducers [ 58 ]. The ability to produce GABA may be a significant trait in the selection of bacterial strains as psychobiotics, as it is thought to be involved in the interaction of gut microbiota with macroorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…GAD genes are discovered in the gut microbiome, and GABA-producing probiotic strains affect health and behavior in animal models. GABA’s sleep-inducing impact has also been demonstrated in animal studies, which revealed that a group fed GABA-containing milk produced more melatonin and serotonin, both of which are regarded as sleep inducers [ 58 ]. The ability to produce GABA may be a significant trait in the selection of bacterial strains as psychobiotics, as it is thought to be involved in the interaction of gut microbiota with macroorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…This means that GABA can be used as a material with enough competitiveness in many domestic drinking populations. Also, Kim et al (2010) conducted study on the sleep-inducing effects of GABA by obtaining the result about the significant increase of melatonin and serotonin in case of eating over a certain amount of GABA produced by lactic acid bacteria through animal test. It means that GABA can get the spotlight as the food ingredient to prevent insomnia increasing rapidly due to such a stress recently if the effectiveness is proven.…”
Section: Efficacies Of Gabamentioning
confidence: 99%
“…Thus, it is also possible that GABA targets other receptors and independent pathways which have direct involvement in sleep physiology. For example, GABA may increase the levels of melatonin and serotonin in the brain adding to its sleep-promoting properties ( Kim et al ., 2010 ). Indeed, there is a need for further mechanistic studies to explain the action of GABA extracts in the brain.…”
Section: Discussionmentioning
confidence: 99%